PERALATAN DAPUR TRADISIONAL SEBAGAI WARISAN KEKAYAAN BUDAYA BANGSA INDONESIA (Traditional of Kitchen Equipment as Cultural Heritage Richness of Indonesia Nation) - Suranny, Lilyk Eka (BALAI ARKEOLOGI PAPUA, 2015)
Traditional kitchen equipment has existed since prehistoric people began to recognize the farming. Along with the development of science and technology, the use of traditional kitchen equipment is being abandoned by the community. Therefore it is necessary to attempt for preserve this traditional kitchen equipment as one of the nations rich heritage. This paper will describe some traditional kitchen equipment, its benefits and the existence in community. Data was collected using observation, interviews and literature study. This study used a qualitative descriptive method. Some traditional kitchen equipment that was found in this study, among others furnace, cormorant, cauldron, wajan, jugs, coconut grated, crock, irus, centong, as well as pestle and mortar. The benefits derived from the use of traditional kitchen equipment is to have a distinctive flavor, safer and environmentally friendly, more economical and preserve the traditions of the ancestors.AbstrakPeralatan dapur tradisional sudah ada sejak manusia prasejarah mulai mengenal bercocok tanam. Seiring dengan perkembangan ilmu pengetahuan dan teknologi, pemakaian peralatan dapur tradisional ini semakin ditinggalkan oleh masyarakat. Oleh karena itu perlu adanya upaya untuk melestarikan peralatan dapur tradisional tersebut sebagai salah satu warisan kekayaan bangsa. Tulisan ini akan membahas beberapa peralatan dapur tradisional, manfaat penggunaannya serta keberadaan di dalam masyarakat saat ini. Teknik pengumpulan data dilakukan melalui pengamatan, wawancara dan studi kepustakaan. Penelitian ini menggunakan metode deskriptif kualitatif. Beberapa peralatan dapur tradisional yang ditemukan dalam penelitian ini antara lain tungku, dandang, belanga, wajan, kendi, parutan kelapa, tempayan, irus, centong, serta cobek dan ulekan. Manfaat yang diperoleh dari penggunaan peralatan dapur tradisional adalah memiliki cita rasa yang khas, lebih aman dan ramah lingkungan, lebih ekonomis serta melestarikan tradisi nenek moyang.